Family Dynamics and Student Well-Being: A Quantitative Study - Bhattarai, Namrata; Bhattarai, Punam (International Research Journal of MMC, 2025)
Family dynamics play a crucial role in shaping individual well-being. This study examines the connection between family structure and well-being, focusing on life satisfaction relationships, financial stability, community support, life satisfaction, meaning and purpose, and general well-being. A cross-sectional survey was conducted of age group 18-25 among 565 students in Kathmandu Valley using opportunity based purposive sampling. Family structure and well-being were assessed using the Adult Wellbeing Questionnaire (24 items). Descriptive and inferential statistics, including Welch’s t-test and ANOVA with Games-Howell post hoc analysis, were employed. Single-parent families reported the highest well-being across multiple domains, whereas blended/stepfamilies had the lowest. Significant differences were found in life satisfaction (p = .005), physical/mental health (p = .005), overall well-being (p = .002), social support (p = .009), meaning/purpose (p = .013), and positive/negative affect (p = .016). Character/caring (p = .121) and relationships (p = .052) were non-significant. Findings highlight the impact of family structure on well-being, emphasizing the need for targeted interventions for children in blended/stepfamilies. Future research should explore underlying mechanisms and develop support strategies to promote well-being and positive development across diverse family types.